Valorization of Polyolefins Dissolved in Light Cycle Oil over HY Zeolites under Fluid Catalytic Cracking Unit Conditions - Arandes, José M. (2003)
A study has been made of the valorization of polyolefins, PE (polyethylene) and PP (polypropylene), dissolved in LCO [light cycle oil obtained as a product stream in a fluid catalytic cracking (FCC) unit] by their cracking on three catalysts prepared based on HY zeolites of different acidity and different porous structure. The reaction has been studied in the 450−550 °C range and under conditions similar to those of the FCC. The determining factor in the performance of the catalyst is the accessibility of the acid sites by the dissolved macromolecular chains, where a moderate acidity of the zeolite is sufficient. Whereas a feed of dissolved PE contributes to a decrease of the yield of coke with respect to that corresponding to the cracking of LCO, a feed of PP increases the yield of coke. The optimum temperature for maximizing the yield of gasoline, and minimizing that of coke, is 450 °C. The gasoline fraction (C5−C12) is mainly aromatic with C8+ components. The stream of gaseous products is largely made up of propylene and butenes.